1963
DOI: 10.1016/0926-6569(63)90237-2
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis of synthetic mixed-acid phosphatides by phospholipase A from human pancreas

Abstract: The Stale ~:)I*teXS~lrl' , IfZ*rchl (l-be .Vethcrlands3 ll{c~,-ivcd June 13th :c~2) SUMM \ NY An inve~tigation wa_~ made int~ the action of a human pancreatic phosph~lipase A on various synthetic ph~x~phatidcs. L-a-l)hosl)hatidyt ethanolamines were readily hydrolvsed in an aqueous system by this enzyme. Synthetic lecithin.,+, h,Jwever, were not attacked in an appreciable rate by the mammalian phospholipase A, contrary to the action J~f the enzymes from animal poisons. Addition of deoxycholate I or synthetic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1963
1963
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Two decades ago it was reported that hydrolysis of acidic phospholipids was more complete than hydrolysis of zwitterionic phospholipids, as judged by chromatographic analysis of the mixture after incubation with human PLA [9]. This apparent preference of pancreatic PLA for anionic phospholipids has been confirmed more recently by kinetic studies on monomolecular surface films [8,17].…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Two decades ago it was reported that hydrolysis of acidic phospholipids was more complete than hydrolysis of zwitterionic phospholipids, as judged by chromatographic analysis of the mixture after incubation with human PLA [9]. This apparent preference of pancreatic PLA for anionic phospholipids has been confirmed more recently by kinetic studies on monomolecular surface films [8,17].…”
Section: Discussionmentioning
confidence: 73%
“…So far, however, kinetic and direct binding studies supporting this hypothesis have been performed largely using either phosphatidylcholines as substrates or substrate analogs carrying the phosphocholine polar head group [7]. Thus the possible importance of lipid surface charge in the mechanism of action of PLA has remained obscure in spite of the fact that, in retrospect, there are clear indications in the older literature [9], that lipid-protein charge interactions might play a role in PLA function.…”
mentioning
confidence: 99%
“…Lysolecithin is formed when pancreatic phospholipase A hydrolyzes the lecithin in bile (49). Its role in the occurrence of BE is by far less understood than that of acid and bile salts but some studies have demonstrated that lecithin is a potentially harmful agent to the esophageal mucosa.…”
Section: Exposure To Trypsinmentioning
confidence: 99%
“…Phospholipases A 2 (PLA 2 s) are small (∼14kDa), stable, calcium‐dependent, disulfide‐rich enzymes that cleave membrane phospholipids at the sn ‐2 position, producing lysophospholipids and free fatty acids 1. The released fatty acids can function as energy stores, second messengers2, 3 and precursors of eicosanoids, which are potent mediators of inflammation 4, 5.…”
Section: Introductionmentioning
confidence: 99%